2018
DOI: 10.3832/ifor2665-011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tree age on chemical compounds of ancient Anatolian black pine (Pinus nigra subsp. pallasiana) needles in Northwest Turkey

Abstract: Plant primary and secondary metabolites are chemical compounds synthesized for essential functions, such as growth and development (primary metabolites), and specific functions, such as pollinator attraction or defense against herbivory (secondary metabolites). Their concentrations in plants are genetically determined, but are also affected by environmental factors. Among these factors, plant age has been reported to influence plant chemical compounds under similar environmental conditions. We aimed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Mean protein content in the total sample was significantly higher in the older age group (III) in both the reference (by 26.5 and 45.5%, respectively, for groups I and II) and experimental samples (by an average of 45.8%) compared to young trees. The higher content of soluble proteins in old trees was also noted in other works (Turfan et al, 2018). The analysis determined that protein amount decreased after an insect attack on the leaves of trees of all age groups in the location where motor vehicle emissions were the main pollutants (L3), but this parameter increased in the location of pipe rolling plant emissions (L5).…”
Section: а вsupporting
confidence: 73%
See 1 more Smart Citation
“…Mean protein content in the total sample was significantly higher in the older age group (III) in both the reference (by 26.5 and 45.5%, respectively, for groups I and II) and experimental samples (by an average of 45.8%) compared to young trees. The higher content of soluble proteins in old trees was also noted in other works (Turfan et al, 2018). The analysis determined that protein amount decreased after an insect attack on the leaves of trees of all age groups in the location where motor vehicle emissions were the main pollutants (L3), but this parameter increased in the location of pipe rolling plant emissions (L5).…”
Section: а вsupporting
confidence: 73%
“…Changes in environmental factors, in particular, the attack of herbivorous insects, affect primary metabolism, such as the rate of photosynthesis, nitrogen uptake, protein content, antioxidant activity, and tree lifespan (Bond et al, 2007;Meinzer et al, 2011;Turfan et al, 2018;Shupranova et al, 2019;Holoborodko et al, 2022). The leaves are the main organ to produce organic matter, and they are the main source of carbohydrates for the plant (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A higher incidence of OQDS for older trees has also been observed in the Gallipoli area, where the decline was first observed. Tree age appears to be related to the differential production of primary and secondary compounds linked to plant metabolism, including the defense system, 12 and differential mutation loads in meristematic tissues. 13 However, specific studies concerning the X. fastidiosa – Olea europea pathosystem are currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This age-related variation has been documented in Anatolian black pine (Pinus nigra subsp pallasiana) and Norway spruce [Picea abiess (L.) Karst.] (Köstner et al, 2002;Turfan et al, 2018). The weakening of the strong relationship between stand age and many metabolites at the overmature stage suggested that metabolic activities changed after the tree attained maturity, although nutrients such as nitrogen and phosphorus continue to accumulate in newly developed needles (Zhou et al, 2016b).…”
Section: Metabolic Profile Of Chinese Fir In Different Growth Stagesmentioning
confidence: 99%